MENDORONG KETERLIBATAN AKTIF KAUM MUDA KATOLIK DALAM BERORGANISASI - Pradana, Dominicus Wahyu; Yuniarto, Antonius (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Catholics youth are the candles of hope and the future sustainability of the Catholic Church. Young people possess enthusiasm and creativity, but this needs to be accompanied by idealism for the progress and development of the Church. Young people are called to participate in the mission of building a better world through the tasks of the Church. However, in practice, many young people are found to prioritize their personal ego without concern for the future of the Church. Therefore, through this activity, it is hoped that young people will become aware of community life, fostering a sense of care that ultimately impacts a better social life. Activities for young people facilitated by the Catholics Youth Organization (OMK) serve as a means to express their faith while also training their leadership, solidarity, and responsibility. Therefore, young people need to be increasingly encouraged to actively engage in non-liturgical church activities.